2020
DOI: 10.1039/d0sc00544d
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and immunological evaluation of new generation multivalent anticancer vaccines based on a Tn antigen analogue

Abstract: A fully-synthetic anticancer vaccine candidate incorporating an hexadecavalent Tn antigen analogue display via oxime linkages induced tumor-specific IgG antibodies and cellular immune responses in mice coadministered with QS-21 as an adjuvant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 89 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…As well as improving strategies for TACA coupling to peptide epitopes that are able to be recognized by T cells, as well as novel polyvalent vaccine development and the characterization of strong and safe immune adjuvants, a promising approach could be vaccine developments based on chemically modified TACAs [337]. Some examples include an oxime-linked Tn analogue [338], a fluoro-substituted Sialyl-Tn [339], and a MUC1-β-TF [340].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…As well as improving strategies for TACA coupling to peptide epitopes that are able to be recognized by T cells, as well as novel polyvalent vaccine development and the characterization of strong and safe immune adjuvants, a promising approach could be vaccine developments based on chemically modified TACAs [337]. Some examples include an oxime-linked Tn analogue [338], a fluoro-substituted Sialyl-Tn [339], and a MUC1-β-TF [340].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Binding to a Tn-specific antibody showed a distinct preference for specific arrangements on the MAP system. The same group has prepared similar systems bearing the sialyl-Tn TACA ( 208 ) as well as Tn conjugated in a natural linkage to serine and one replaced with an oxime unit, where they showed that the oxime-linked Tn had superior immunotherapeutic properties in vivo ( 209 ).…”
Section: Glyco-nanotechnology and Cancer Immunotherapymentioning
confidence: 99%
“…The low immunogenicity of tumor-associated carbohydrate antigens (TACAs), including the Tn antigen, is one of the major obstacles in the development of TACA-based antitumor vaccines. The immunogenicity can be enhanced by conjugation of TACA to a natural or synthetic immunostimulant carrier or by synthetic modification of TACA if the modified antigen is recognized as foreign by the immune system, and the elicited immune response is cross-reactive to the native antigen expressed in the tumor tissue. The fluorination of TACAs is an attractive approach because fluorinated carbohydrate epitopes are structurally similar to natural epitopes, , thus increasing the likelihood of generating cross-reactive antibodies. In addition, deoxyfluorination (the replacement of an OH group with fluorine) increases the resistance of the glycosidic bond to hydrolysis, which can help overcome the sensitivity of carbohydrate-based vaccines to metabolic degradation . The synthesis of deoxyfluorinated TACA is challenging.…”
Section: Introductionmentioning
confidence: 99%